Physical and Sensory Characteristics of Food Bar Based on Beneng Taro (Xanthosoma undipes K. Koch) and Soy Protein Isolate - Fany Dwi Wahyuni; Fitria Riany Eris; Nia Ariani Putri; Rifqi Ahmad Riyanto (Food ScienTech Journal, 2022)
Beneng taro, a local food plant in Banten Province, has enormous potential to be developed as an effort to diversify food, one of which is used as a raw material in the manufacture of food bars. Ingredients formulation and roasting temperature can affect the characteristics of the resulting food bar. Therefore, researchers consider it necessary to conduct research related to the physical and sensory characteristics of food bars based on beneng taro, mocaf and soy protein isolate as one of food diversification, as well as the best formulation and roasting temperature of the food bar. This study used a completely randomized split plot design with two factors, namely roasting temperature and ingredients formulation. The L* value, a* value, and texture were all significantly impacted by the roasting temperature, according to the results. Meanwhile, the L*, a*, and b* values were significantly impacted by the addition of beneng taro flour and soy protein isolate. The a* value, b* value, as well as the panelists' evaluation of the color, texture, and overall parameters are significantly impacted by the interaction between the two factors. The formulas for the chosen food bars contained 30% taro flour and 70% soy protein isolate, and they were baked at 140 °C (S2R2) with the following characteristics: texture 26,59 N; L* value 46,75; a* 14,99; b* 32,17; and the value of preference for color, taste, aroma, texture and overall is 2,23; 2,10; 2,23; 2,15; and 2,25.